Kajian Geometri Peledakan untuk Menapatkan Fragmentasi yang Optimal Pada Penambangan Batu Andesite PT. Koto Alam Sejahtera, Kabupaten 50 Kota Provinsi Sumatera Barat - Mia Fazira; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Andesite Stone Mining at PT. Koto Alam Sejahtera with an open mining system using the Quarry mining method. The percentage of boulder-sized blasting fragmentation produced currently in the field is ± 35% as a result the diggability of the loading and unloading equipment is not maximal and the planned productivity of the loading and unloading equipment planned by the company at 100 bcm / hour is not achieved. This study aims to design a new blasting geometry to obtain optimal fragmentation results so that loading activities are effective and productivity targets are achieved. The research method was carried out by giving recommendations on blasting geometry based on R.L.'s theory. Ash and C.J. Konya and carried out the application of one of the blasting geometry designs in the field so that the optimum blasting geometry design from one of the blasting geometry designs can be applied in the future for the company. Basic results of field application to one of the blasting geometry design proposals are: burden: 2 m, space: 2 m, stemming: 1,4 m, subdrilling: 0,6 m, level height: 6 m, depth of blast hole 6,5 m, powder colomn: 5,1 m, and powder factor: 0,68 kg / m3 where the boulder size fragmentation resulting from the desktop split software analysis is 0%. The digging time produced is 9,23 seconds, the bucket fill factor is 60%, and the productivity of the digging tool is 108,54 bcm / hour.Keywords: Blasting Geometry, Blasting Result Fragmentation, Digging Time, Bucket Fill Factor, Productivity of Digging Tools